Exploring the Patients’ Mental Model of the Sunshine Social Welfare Foundation’s Support Group on Facebook: A ZMET Approach - Yi-Chiao Vicky Tseng; Ming-Hsin Phoebe Chiu (Jiàoyù zīliào yǔ túshūguǎn xué, 2020)
With popularizing the Internet, more and more resources and services have emerged along with social networking sites. The Sunshine Social Welfare Foundation’s online support group on Facebook was set up for patients with burn and scald injuries. It provides a platform for patients to possibly restart a new life via support groups. The purpose of this study is to explore the participants’ mental model of Sunshine Social Welfare Foundation Support Group on Facebook, and to understand the underlying thoughts and needs of patients of burn and scald injuries by using the Zaltman Metaphor Elicitation Technique (ZMET). This study recruited 8 patients as research participants and collected a total of 72 pictures. The ZMET was applied to understand each participant’s thoughts, while metaphor analysis was used to investigate the results and core values, which were then drawn into consensus map for further analysis. In conclusion, three main findings are as follows: (1) The mental model of participants on online support group is to get back to their normal life, participate in education and learning, and need spiritual support. (2) Patients receive hope and goal of life from online support group. (3) The participants need the online support group for enhancing themselves, to promoting social values and developing future. According to these results, some suggestions are made for patients of burn and scald injuries and social welfare organizations and departments.